2017
DOI: 10.1002/lno.10511
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting NPQ dynamics and xanthophyll cycling in a motile and a non‐motile intertidal benthic diatom

Abstract: Diatoms living in intertidal sediments have to be able to rapidly adjust photosynthesis in response to often pronounced changes in light intensity during tidal cycles and changes in weather conditions. Strategies to deal with oversaturating light conditions, however, differ between growth forms. Motile epipelic diatoms can migrate to more optimal light conditions. In contrast, non-motile epipsammic diatoms appear to mainly rely on higher Non-Photochemical Quenching (NPQ) of chlorophyll a fluorescence to dissip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 65 publications
4
44
0
Order By: Relevance
“…, Blommaert et al. ), and ii) sea‐ice for a microalgal community dominated by diatoms ( Detonula confervacea , slope of 2.03; Katayama and Taguchi ) which are exposed to subzero temperatures, very high salinity and potentially moderate irradiances when the snow cover starts to melt in spring. High QEs of ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, Blommaert et al. ), and ii) sea‐ice for a microalgal community dominated by diatoms ( Detonula confervacea , slope of 2.03; Katayama and Taguchi ) which are exposed to subzero temperatures, very high salinity and potentially moderate irradiances when the snow cover starts to melt in spring. High QEs of ca.…”
Section: Resultsmentioning
confidence: 99%
“…15 to 45 min on, depending on the species; see Blommaert et al. for the most recent example). This feature, as well as the lower QE under high light acclimation, have been attributed to the synthesis of additional Dt molecules that do not bind to the LHC system, and therefore, do not participate to NPQ (Schumann et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity for flexible NPQ is mainly defined by the xanthophyll cycle (XC) pigment diatoxanthin (Dtx) produced via de-epoxidation of diadinoxanthin (Ddx) (Lavaud and Goss, 2014;Barnett et al, 2015;Goss and Lepetit, 2015;Blommaert et al, 2017), and the presence of Light-Harvesting Complex X (LHCX) proteins (Bailleul et al, 2010;Ghazaryan et al, 2016;Taddei et al, 2016Taddei et al, , 2018Lepetit et al, 2017). While the XC in benthic diatoms has been well-studied in natural communities (van Leeuwe et al, 2008;Jesus et al, 2009;Serôdio et al, 2012;Laviale et al, 2015) and more recently also using unialgal isolates Blommaert et al, 2017), our current knowledge about LHCX proteins as an NPQ regulator is mostly based on studies of planktonic diatoms (Nymark et al, 2009(Nymark et al, , 2013Büchel, 2014;Lavaud and Goss, 2014;Valle et al, 2014;Dong et al, 2015;Goss and Lepetit, 2015;Ghazaryan et al, 2016;Grouneva et al, 2016;Lepetit et al, 2017;Taddei et al, 2018Taddei et al, , 2016. The latter includes studies on the pennate model diatom Phaeodactylum tricornutum which to date has only been isolated from water samples from various coastal environments, but may have a benthic growth phase as well (De Martino et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using immuno-blotting revealed the presence of several light-regulated LHCX-proteins in natural communities and isolates of the microphytobenthic diatom S. robusta, of which some differ in size from P. tricornutum homologs Blommaert et al, 2017). To date, however, nothing is known about the diversity, organization and transcriptional regulation of these LHCX proteins in truly benthic diatoms.…”
Section: Introductionmentioning
confidence: 99%